Fit for purpose? Exploring competence in quality management. Issue 3 (13th September 2019) - Martin, Jason; Elg, Mattias; Gremyr, Ida
Abstract : Purpose: The purpose of this paper is to use competence theory to explore the fit between actual competencies of quality management (QM) practitioner and the perception of QM competence needs in organisations. Design/methodology/approach: This paper is based on a cross-case quantitative study design featuring a survey of QM practitioners ( n  =   249) within eight large Swedish organisations. The research instrument was a questionnaire covering seven themes within QM. The analysis is based on descriptive statistics. Findings: The results show that while the perception of formal QM competence may seem sufficient, the evolving nature of QM requires knowledge, skills and attitudes that are also apt for more external and explorative perspectives. There is a bias towards competence for exploitative QM rather than explorative QM. Organisational logics preserving and possibly reinforcing a perceived "competence lag" in organisations are identified and described. Originality/value: Few empirical studies within QM explore the competencies required for QM practices. This paper contributes to QM research in providing arguments for adopting the competence theory as a foundation for organising current and future QM work.